New insights into the autecology of the two sympatric fish species Notothenia coriiceps and N. rossii from western Antarctic Peninsula: A trophic biomarkers approach - Moreira, María Eugenia; Martínez Novillo, Manuel; Mintenbeck, Katja; Alurralde, Roque Gastón; Barrera Oro, Esteban; De Troch, Marleen (Polar Biology)
Biomarker analysis, especially fatty acids (FA) and stable isotopes (SI), has become a useful tool to elucidate the flow of energy and trophic interactions in an ecosystem and to analyse the diet of species that are hard to observe whilst feeding. Herein we compare FA profiles and SI composition (nitrogen, δ15N and carbon, δ13C) of muscle tissue from two sympatric Antarctic fish species—Notothenia rossii and N. coriiceps—that are key components in the inshore ecosystem of the South Shetland Islands. For both nototheniids, potential benthic food sources (algae, amphipods, polychaetes and gastropods) were screened in order to re-evaluate their trophic position (TP) and the energy flow. Significant differences in FA and SI composition between the two fish species were found. Notothenia rossii showed a higher total FA concentration, with high levels of polyunsaturated FA. Conversely, the potential food sources tested showed low concentrations of these FAs. This could indicate that both nototheniids are feeding mainly on another food source or that FA bioconversion takes place. While the FA results might suggest a possible trophic niche segregation between N. rossii and N. coriiceps, both species occupy a similar trophic position. Furthermore, we found a 50-times higher total concentration of monounsaturated FA in N. rossii than in N. coriiceps that can be related to the higher buoyancy capacity of the former. Trophic biomarkers did not elucidate the main prey item as lipid source for N. rossii and N. coriiceps, suggesting that other food sources and potential fatty acid bioconversion should be further investigated. Fil: Moreira, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Cientifico Tecnolológico Mar del Plata. Instituto de Investigaciones en Biodiversidad y Biotecnología. Laboratorio de Biología Funcional y Biotecnología; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: ...